(untitled) (Portuguese Journal of Family Medicine and General Practice, 2016)
Objectives: Falls are defined as events in which a person comes to rest inadvertently on the ground or floor or other lower level. They do not happen by chance, but can be predicted through the assessment of risk factors. The elderly population is more vulnerable. It is estimated that 30% of people aged 65 or more fall at least once a year. This represents a potentially preventable cause of disability and high health care costs. The aim of this study is to determine the benefits of physical exercise (PE) in the prevention of falls in the elderly. Data sources: MEDLINE and evidence-based medicine databases. Review methods: Research of clinical guidelines, meta-analyses (MA), systematic reviews (SR) and randomized controlled clinical trials, published between January 2010 and September 2014, using the MeSH terms: ACCIDENTAL FALLS, ACCIDENT PREVENTION, AGED and EXERCISE. Strength of Recommendation Taxonomy (SORT) was utilized for the assignment of levels of evidence and strength of recommendations. Results: We found 203 articles. Five met the inclusion criteria, including three MA and two SR. There is evidence that exercise programs to prevent falls in older people not only reduce the incidence of falls but also prevent injuries arising from falls. Many of the risk factors for falls are correctable by well-designed exercise programs. These are equally effective if practiced at home. The most effective type of PE in the prevention of falls in the elderly is balance training. PE programs are more effective if prolonged in time and of greater intensity (a greater number of hours and at least twice a week). Conclusions: PE programs should be recommended because they are effective in decreasing the number and risk of falls in the elderly (Strength of Recommendation A).